Effectiveness of Dry Needling in Bothersome Chronic Tinnitus in Patients with Myofascial Trigger Points - Carla Alexandra Campagna; Juliana Anauate; Laura Garcia E. Vasconœlos; Jeanne Oiticica (International Archives of Otorhinolaryngology, 2022)
Introduction Therapeutic dry needling (DN) is effective in reducing the discomfort of chronic somatosensory tinnitus in patients with myofascial trigger points (MTP)s. Objective To evaluate the efficacy of DN in chronic somatosensory tinnitus discomfort in patients with MTP. Methods Placebo-controlled paired trial that included 16 patients with a diagnosis of somatosensory chronic tinnitus and with the presence of at least one active or latent MTP. Treatment was performed in two phases: (1) four sessions (one session per week for four consecutive weeks) of placebo DN and (2) four sessions of therapeutic DN with a gap (washout) of 15 days between these phases. Results The Tinnitus Handicap Inventory (THI) variable and its emotional domain had a statistically significant reduction in therapeutic DN when compared with placebo DN (p = 0.024 and p = 0.011, respectively). The tinnitus visual analogic scale (VAS) signaled a reduction in tinnitus discomfort when compared with moments before and after therapeutic DN (p < 0.05). Conclusion The therapeutic DN technique for MTP in patients with chronic tinnitus of somatosensory origin proved effective in reducing symptom discomfort, as measured by the THI (total score) and its emotional domain when compared with placebo DN.